WRITING AND THE WRITER (Author: Frank Smith) - Bockus, E.C. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1983)
Frank Smith. WRITING AND THE WRITER. Toronto and New York: Holt, Rinehart and Winston, 1982. 257 pp. $20.25.